ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG PERUSAHAAN DENGAN PECKING ORDER THEORY PADA PERUSAHAAN WHOLESALE DAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2016 - Nadya Prihartini, Nurhalis (Departemen Manajemen, 2018)
Abstract: Debt policy is one of the decisions related to company funding taken by the manager. This study aims to determine the effect of profitability, asset structure, and growth rate by using variable control of firm size and sales growth on debt policy. Using multiple linear regression analysis method, the result showed that profitability and asset structure had a significant negative effect to company policy. Company growth rate, firm size, sales growth have a significant positive effect on debt policy. This is in accordance with the assumption of pecking order theory. Meanwhile, the Independent sample T-test shows that there is no real difference between the debt policy of wholesale and retail companies listed in Indonesia Stock Exchange.